Global Health Implications of Nutrient Changes in Rice Under High Atmospheric Carbon Dioxide. Issue 7 (31st July 2019) - Smith, M. R.; Myers, S. S.
Abstract: A growing literature has documented that rising concentrations of carbon dioxide in the atmosphere threaten to reduce the iron, zinc, and protein content of staple food crops including rice, wheat, barley, legumes, maize, and potatoes, potentially creating or worsening global nutritional deficiencies for over a billion people worldwide. A recent study extended these previous nutrient analyses to include B vitamins and showed that, in rice alone, the average loss of major B vitamins (thiamin, riboflavin, and folate) was shown to be 17–30% when grown under higher CO2 . Here, we employ the EAR cut‐point method, using estimates of national‐level nutrient supplies and requirements, to estimate how B vitamin dietary adequacy may be affected by the CO2 ‐induced loss of nutrients from rice only. Furthermore, we use the global burden of disease comparative risk assessment framework to quantify one small portion of the health burden related to rising deficiency: a higher likelihood of neural tube defects for folate‐deficient mothers. We find that, as a result of this effect alone, risk of folate deficiency could rise by 1.5 percentage points (95% confidence interval: 0.6–2.6), corresponding to 132 million (57–239 million) people. Risk of thiamin deficiency could rise by 0.7 points (0.3–1.1) or 67 million people (30–110 million), and riboflavin deficiency by 0.4 points (0.2–0.6) or 40 million people (22–59 million). Because elevated CO2 concentrations are likely to reduce B vitamins in other crops beyond rice, our findings likely represent an underestimate of the impact of anthropogenic CO2 emissions on sufficiency of B vitamin intake. Plain Language Summary: Rice is a crucially important food globally, providing more calories than any other. Meanwhile, the environmental conditions where we grow rice are changing as global carbon dioxide levels rise. Recently, researchers have shown that rice grown under CO2 levels that we may reach by as soon as 2050 lower rice's content of many important nutrients—riboflavin, thiamin, and folate—by 17–30%. These nutrients are vital for proper neural and cardiovascular system function, and deficiencies in folate among mothers have been linked to neural birth defects in their children. We find that even moderate losses of these nutrients in rice caused by higher CO2 could have potentially large impacts on global health, placing tens of millions of people at new risk of deficiencies in one or more of these nutrients. However, we estimate that the rise in folate‐related birth defects may be relatively small due to a mismatch between the countries becoming newly deficient and those already suffering from high rates of such defects. However, these results only represent one health outcome, and the combined health effects of multiple new deficiencies may emerge a significant threat to global health. Key Points: Global CO2 levels that may be reached as soon as 2050 have been shown to lower the B vitamin content of rice by 17–30% These losses may cause 132 million people globally to become at risk of deficiency in folate, 67 million in thiamin, and 40 million in riboflavin Highly affected regions are those that are mostly nutritionally reliant on rice: Africa (West and East) and Asia (Southeast, East, and South)